1999
DOI: 10.1136/oem.56.9.577
|View full text |Cite
|
Sign up to set email alerts
|

Lymphohaematopoietic malignancy around all industrial complexes that include major oil refineries in Great Britain.

Abstract: Objectives-To examine the incidence of lymphohaematopoietic malignancy around industrial complexes that include major oil refineries in Great Britain after recent public and scientific concern of possible carcinogenic hazards of emissions from the petrochemical industry. Methods-Small area study of the incidence of lymphohaematopoietic malignancies, 1974-91, within 7.5 km of all 11 oil refineries (grouped into seven sites) in Great Britain that were operational by the early 1970s and processed more than two mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…A study of the health of residents near the industrial, petrochemical, and steel complex at Teesside, including the coke works, showed no clear evidence of any health effect except perhaps for lung cancer in women and a suggestion of a gradient in adults and children for self-reporting of more than 12 asthma attacks in the previous year 3031 The petrochemical plant was also included in a national study of lymphohaematopoietic cancers near industrial complexes containing major oil refineries in Great Britain, but the results were largely negative 32. A study near the Monkton coke works in South Tyneside, North East England (which is now closed and therefore not included in the present study) also found significant excess reporting of respiratory and related problems among children living near the plant 16…”
Section: Discussionmentioning
confidence: 99%
“…A study of the health of residents near the industrial, petrochemical, and steel complex at Teesside, including the coke works, showed no clear evidence of any health effect except perhaps for lung cancer in women and a suggestion of a gradient in adults and children for self-reporting of more than 12 asthma attacks in the previous year 3031 The petrochemical plant was also included in a national study of lymphohaematopoietic cancers near industrial complexes containing major oil refineries in Great Britain, but the results were largely negative 32. A study near the Monkton coke works in South Tyneside, North East England (which is now closed and therefore not included in the present study) also found significant excess reporting of respiratory and related problems among children living near the plant 16…”
Section: Discussionmentioning
confidence: 99%
“…However, a similarly designed study, also in Britain, of lymphohematopoietic malignancies around oil refineries did not find an increased cancer risk among children (Wilkinson et al 1999). Previous epidemiologic studies have also found associations between childhood cancer and parental occupational exposure to petroleum hydrocarbons (Colt and Blair 1998;Savitz and Chen 1990), but occupational exposure levels are generally much higher than those found in outdoor air.…”
mentioning
confidence: 90%
“…The researches indicated petrochemical industries not only led to accumulation of toxic elements in environment, but also increased the risk of contracting cancers and affected the birth of infants for inhabitants living around (Bosco et al 2005;Lin et al 2001;Nadal et al 2004Nadal et al , 2007Relić et al 2005;Wilkinson et al 1999;Yang et al 2004). One of the largest petrochemical complexes in China was constructed in Huangpu District of Guangzhou City, China in 1973.…”
mentioning
confidence: 99%